Who Is the Rightful Owner? Young Children’s Ownership Judgments in Different Transfer Contexts - Li, Zhanxing; Qi, Minli; Yu, Jing; Zhu, Liqi (Frontiers in Psychology, 2018)
This study aimed to examine whether Chinese preschoolers understand that ownership can be transferred in different contexts. The study participants were 3- to 5-year-old Chinese children (n = 93) and adults (n = 34). With four scenarios that contained different transfer types (giving, stealing, losing, and abandoning), participants were asked four questions about ownership. The results indicated that preschoolers’ ability to distinguish legitimate ownership transfers from illegitimate ownership transfers improved with age. Three-year-olds understood that ownership cannot be transferred in a stealing context, but the appropriate understanding of ownership was not attained until 4 years old in a giving context and 5 years old in losing and abandoning contexts, which is similar to the adults’ performance. In addition to the first possessor bias (a tendency to judge the first possessor as the owner) found in previous studies, 3-year-olds also displayed a loan bias (a tendency to believe everything that is transferred should be returned) in the study. The findings suggest that the developmental trajectories of preschoolers’ understanding of ownership transfers varied across different contexts, which may relate to children’s ability to consider the role of intent in determining ownership and parents’ disciplinary behavior. Both cross-cultural similarities and differences are discussed.